2013
DOI: 10.4103/0974-7796.110014
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord prolapsed through urethra: An unusual presentation of a vesico-uterine fistula

Abstract: Umbilical cord prolapse occurs when a loop of cord is present below the presenting part when the amniotic membranes are ruptured. The incidence is 0.2% of total births. The case presented here is unusual because the definition of cord prolapse cannot be applied to it and the lady did not complain of any history of urinary incontinence or hematuria. The presentation of umbilical cord through maternal urethra led to the speculation of an opening between the anterior uterine wall and the bladder. Fetal demise was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…An intact fetus was discovered within the urinary bladder 20 years after cesarean surgery, as observed by H. Armstrong et al (2). Kamil and El Mekresh described a case where the umbilical cord protruded through the urethral meatus (7), we reported unusual special presentation for protrusion of the amniotic sac through the urethral meatus which is unusual important complication of VUF. Kives et al described same presentation (4).…”
Section: Discussionsupporting
confidence: 63%
“…An intact fetus was discovered within the urinary bladder 20 years after cesarean surgery, as observed by H. Armstrong et al (2). Kamil and El Mekresh described a case where the umbilical cord protruded through the urethral meatus (7), we reported unusual special presentation for protrusion of the amniotic sac through the urethral meatus which is unusual important complication of VUF. Kives et al described same presentation (4).…”
Section: Discussionsupporting
confidence: 63%
“…They state that a vesicouterine fistula should be part of the differential diagnosis of urinary incontinence. There are some reports of unusual clinical presentations: Kamil and El Mekresh 36 report a case of protrusion of the umbilical cord through the urethral meatus. The patient, a 31-year-old woman, had a bladder injury during her second cesarean section, which was performed at 24 weeks of gestation for antepartum hemorrhage.…”
Section: Case Reportmentioning
confidence: 99%
“…The authors made the hypothesis that the fistulous orifice was reopened due to the distention of the uterine wall during pregnancy. 36 Lesovoy et al 37 reported a case of “fetus in the bladder.” A 39-year-old woman had a bladder injury during her second cesarean, which was promptly corrected. She was discharged without symptoms, but three months later, she presented with symptoms suggestive of vesicouterine fistula, and the diagnosis was confirmed through a cystoscopy.…”
Section: Case Reportmentioning
confidence: 99%
“…Signs and symptoms may occur soon after delivery, or they can take years to develop, and are often associated with worsening of life quality and psychological distress. ( 2 ) Besides this syndrome, endometriosis, obstructed labor, tuberculosis, and malignancy are other etiologies. Diagnosis is made by cystoscopy, hysterography, or excretory urography; however, in some cases, transvaginal ultrasound, magnetic resonance imaging (MRI) or helical computerized tomography scan have a major role.…”
Section: Introductionmentioning
confidence: 99%